ANALISIS KINERJA AIR HEATER DI PLTU ASAM-ASAM UNIT 2 - Irawan Irawan; Aqli Mursadin (JTAM ROTARY, 2019)
Indonesia as one of the largest coal producers utilizes this advantage by establishing a steam power plant, one of which is Borneo south PLTU power plant PT.PLN (persero) south of Borneo and Central Borneo Asam-Asam generation sector. One important component of PLTU is air heater to raise the combustion air temperature. Initial heating of ljungstrom type lattest regenerative air  heater in PLTU Asam-Asam unit 2 is carried out cleaning and maintenance on seal and gas side surfaces to optimize heat transfer coefficient and ratio of air intake ratio exposed by forced draft fan and air heated by flue gas in heater air heater elements and transferred to the combustion chamber to make efficient use of new fuel. Measurements were carried out on August 9, 2017 for 2 hours to find out the average value of heat transfer coefficient and temperature comparison of entry and exit from air heater of Asam-Asam unit 2 steam power plant. This research was conducted to find out the value of heat transfer coefficient and air temperature ratio with measurement on the inlet and outlet for two hours. The results of the air heater performance analysis in in PLTU Asam-Asam unit 2 steam power plant in terms of the highest heat transfer coefficient was 62.75 W/m^2.℃ at 2:04 PM, while the lowest heat transfer coefficient was 62.37 W/m^2.℃ at 3:10 PM, and the average heat transfer coefficient is 62.50 W/m^2.℃ . While the highest water heater ratio 9.70 at 3:44 PM and the lowest ratio 8.32 at minute 3:09 PM, and the average water heater ratio 9.01. Heater water heater elements in good condition and performance in receiving and releasing heat. Keywords: Air Heater,  Heat Transfer Coefficient, Temperature Ratio,  Heating  Elements